Anti-Migration as a Threat to Internationalization? A Review of the Migration-Internationalization Literature - Andreas Hatzigeorgiou; Magnus Lodefalk (Global Labor Organization (GLO), 2018)
Does anti-migration sentiment threaten internationalization? One major pro-Brexit argument was that it would enable more control over immigration. The most recent US presidential election also focused on immigration. Anti-migration sentiment could be a threat to internationalization, given that migrants can help lower the costs of internationalization. Since trade contributes to economic growth, this could, in turn, impede economic development. Despite extensive literature on the migration-trade nexus, there are few examples of policymakers highlighting the role of migration for internationalization. One possible explanation is the absence of an accessible survey of the available theory and evidence on this relationship, and this article intends to bridge the gap. We review and discuss over 100 papers published on the subject, from pioneering country-level studies to nascent firm-level studies that utilize employer-employee data. To our knowledge, this is the first paper offering a wide-ranging review of the different strands of theory on the relationship between migration and internationalization, as well as new empirical findings. Although the evidence suggests that migration can facilitate internationalization we also note substantial gaps and inconsistencies in the extant literature. The aim of this article is to encourage future research and assist policymakers in their efforts to promote internationalization.
Keywords: D20; D80; F14; F16; F22; F23; J61; 330; Migration; networks; information; trade; foreign direct investment